Evaluation of clinical pathway for laparoscopic appendicectomy in HUSM - Chin, Chong Yi (2018)
A clinical pathway is a multidisciplinary plan of care based on best clinical practice for a specified group of patients with a particular diagnosis. It is designed to optimize resource utilization, and maximize quality of care. The efficacy and benefit of clinical pathway has been studied extensively in a few surgical fields and proven to be beneficial. However, the efficiency and benefit of clinical pathway implementation for laparoscopic appendicectomy in HUSM has yet to be studied. A clinical pathway for laparoscopic appendicectomy for acute appendicitis was developed in 2012 by the surgical team of HUSM in collaboration with the nursing staff, with a target length of stay of 3 days. The aim of this study was to determine the cost of treatment of appendicitis patients under implementation of standard CP for laparoscopic appendicectomy in HUSM and to evaluate spectrum of variance in treatment of appendicitis under this clinical pathway. All patients aged 12 or more, who were admitted to HUSM for suspected acute appendicitis and undergone treatment according to the clinical pathway from June 2014 until June 2016 was included in this study. Patients who had laparoscopic appendicectomy as part of other procedure, who were found intra-operatively to have diagnosis other than acute appendicitis, with significant co-morbid, and who require ICU care were excluded. The datasheet documents of the clinical pathway were collected, data on the treatment, cost of treatment, and variances in length of stay (LOS), cost and treatment were analysed. 121 samples were collected and analysed. The mean cost of treatment was RM 1736.02. The mean LOS was noted to be 2.75 days, with standarddeviation of 0.933 days. Only 12.4% of patients had LOS of more than 3 days (negative variance), while 41.3% of patients actually had positive LOS less than 3 days. This means only 46.3% of patients had LOS of 3 days as per the pathway. Majority of the cause for negative LOS were due to delay of surgery for more than 1 day after patient was posted for surgery. Another major variance is in initiation of antibiotics, whereby only around 12% ofpatients receive antibiotics upon admission as per pathway. This study has identified the cost of treatment, and major variances in length of stay and certain treatment. Several modifications in the clinical pathway and changes in its implementation may be needed to improve its efficiency and benefit.